Mandibular symphyseal fusion in fossil primates: Insights from correlated patterns of jaw shape and masticatory function in living primates. Issue 2 (13th March 2020) - Knigge, Ryan P.; Vinyard, Christopher J.; McNulty, Kieran P.
Abstract: Objectives: Variation in primate masticatory form and function has been extensively researched through both morphological and experimental studies. As a result, symphyseal fusion in different primate clades has been linked to either the recruitment of vertically directed balancing‐side muscle force, the timing and recruitment of transversely directed forces, or both. This study investigates the relationship between jaw muscle activity patterns and morphology in extant primates to make inferences about masticatory function in extinct primates, with implications for understanding the evolution of symphyseal fusion. Materials and methods: Three‐dimensional mandibular landmark data were collected for 31 extant primates and nine fossil anthropoids and subfossil lemur species. Published electromyography (EMG) data were available for nine of the extant primate species. Partial least squares analysis and phylogenetic partial least squares analysis were used to identify relationships between EMG and jaw shape data and evaluate variation in jaw morphology. Results: Primates with partial and complete symphyseal fusion exhibit shape‐function patterns associated with the wishboning motor pattern and loading regime, in contrast to shape‐function patterns of primates with unfused jaws. All fossil primates examined (except Apidium ) exhibit jaw morphologies suggestive of the wishboning motor pattern demonstrated in living anthropoids and indriids. Discussion: Partial fusion in Catopithecus, similar to indriids and some subfossil lemurs, may be sufficient to resist, or transfer, some amounts of transversely directed balancing‐side muscle force at the symphysis, representing a transition to greater reliance on transverse jaw movement during mastication. Furthermore, possible functional convergences in physiological patterns during chewing (i.e., Archaeolemur ) are identified.